Statera and Hydraulis: Two Drawings by Daniele Barbaro on the Margins of the 1511 Edition of Vitruvius from the Pushkin State Museum of Fine Arts Collection - Igoshina, Ekaterina P. (Actual Problems of Theory and History of Art, 2023)
The Pushkin State Museum of Fine Arts Research Library holds a 1511 Latin edition of the “Ten Books on Architecture” treatise written by ancient Roman architect Marcus Vitruvius Pollio. The copy has numerous handwritten notes, mostly in Latin, which in 2020 were attributed to Venetian humanist Daniele Barbaro (1514–1570). Aside from the notes, in the margins of the treatise, Barbaro left 23 drawings. The subjects of the article are the two drawings in the margins of Book 10, dedicated to description of mechanisms. The first drawing, on the obverse of Sheet 98, accompanies the text of Chapter 8, “On the Straight and Circular Motions That Are Required to Lift Weights”. In this drawing, Barbaro depicted a steelyard (statera) — an ancient Roman mechanism for lifting and weighting multi-format objects. The second drawing placed in the obverse of Sheet 103, approximately in the middle of Chapter 13, “On the Hydraulic Machines Used to Make Organs”, depicts a water organ (hydraulis). The comparison of the drawings with the text from the treatise by Vitruvius showed that both drawings are closely related to its content and, just as most handwritten commentaries, reflect the reaction of the Venetian humanist to the text he read. However, in both cases, the pictures do not illustrate certain passages of text, and, moreover, they even contradict the text by Vitruvius in some measure. None of the two drawings can be called a preparatory sketch for the engraved illustrations from the “Commentary to Vitruvius” by Daniele Barbaro (Venice, 1556 and 1557), most of which were executed by architect Andrea Palladio (1508–1580): the image of statera copied from the treatise by Jean Borrel, “On Scales and Steelyards” (Lion, 1554), is provided by the humanist in addition to the engraving by Fra Giocondo, and by drawing a hydraulic organ, Barbaro suggests that the redactor of the text and the author of the engravings of 1511 did not exert enough effort in illustrating the corresponding fragment of the antique treatise.This research project on the Moscow exemplar of Fra Giocondo’s 1511 edition of Vitruvius was realised through the financial support of the Pushkin Museum patron company “Vympel”. The project team consists of Ekaterina Igoshina, Anna Markova, Ilya Anikyev, Julia Krasnobayeva, Aliya Yamalieva.
Keywords: Daniele Barbaro; Vitruvius; architectural treatise; marginalia; commentary; drawing; hydraulis; statera; Jean Borrel; Heron of Alexandria